Effect of different Nitrogen levels and Bio-fertilizers on yield and economics of feed barley - Neelam, N; Singh, Bhagat; Khippal, Anil; Mukesh, M; Satpal, S (Journal of Cereal Research, 2018)
The field experiment was carried out during the Rabi season of 2015-16 and 2016-17 at CCS Haryana Agricultural University, Hisar. It was laid out in split plot design replicated thrice with three nitrogen levels (50,75 and 100 percent of RDN) in main plots and five different biofertilizers alone or in combination (control, Azotobacter, Azotobacter + PSB, PSB and Biomixie Azotobacter + PSB + Azospirillum) in sub plots. Based on the research investigation, it was found that increasing levels of nitrogen and biofertilizers had significant effect on yield and yield attributing characters. The grain yield was affected significantly as the level of nitrogen increased from 50 to 100 percent. Highest grain yield and biological yield of 52.29 qha-1 and 124.50 qha-1 were recorded with the application of 100% RDN, which were significantly higher over lower doses of nitrogen. The maximum number of effective tillers m-2 (413), grains per ear head (50.91) and 1000-grains weight (43.84 g) were also found maximum at 100% RDN. Maximum Net returns (45732) and B:C ratio (2.40) were achieved when 100% RDN was applied. Among different bio-fertilizers, Biomix recorded significantly higher yield attributes (effective tillers m-2, number of grains per spike and test weight). Grain and biological yield of 51.32 q ha-1 and 120.01 q ha-1, respectively were recorded under Biomix, which were at par with Azotobacter + PSB treatment. Highest net returns of ₹41897 and B:C ratio of 2.28 were obtained with the application of Biomix in barley crop. Doi.org/10.25174/2249-4065/2018/84510